Produções discursivas do horror: materialidade fílmica e memória na trilogia de Zé do Caixão - Santos, Janaina de Jesus [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study has theoretical and methodological support in French Discourse Analysis as have been developed in Brazil, taking as axis notions of discursive memory, intericonicity and subjectivity. The corpus of our research consists of excerpts from the films that make up the Coffin Joe Trilogy by José Mojica Marins, namely: At midnight I'll take your soul (1964), This night I’ll possess your corpse (1967) and Embodiment of evil (2008), in order to understand the production of horror through discursive memory in materiality of the films we set out to analyze. The scenes were selected considering the classics of horror narratives, observed both in literature and film elements, and those that reveal the artistic uniqueness of the work of the filmaker. We explore horror production in discursive materiality, highlighting the notions of memory and intericonicity. For this, first we comprehend discursive memory in film visuality, to know regularity in discursive working of cinema strategies. Next, we reflect about horror discourse as historical practices, thinking of discursive order in cenography and sound track in the period between XX century second half and XXI beginning. Then, we explore sense production of horror in cinema materiality, highlighting the notions of memory and intericonicity in film visuality. And so we was conducted by those questions: a) what are theory methodological work to analyze discursive working of cinema strategies?; b) how it produces subjectivity in discourse and filmic visuality; and c) how discursive materiality in film revivals discourses and produces horror senses. The investigation of plans and sequences points to specific place to the subject transgressor as who emerges discourses about monstrosity and horror in transgressor practices to Jewish-Christian moral. In the Marins films, horror construction is in Zé do Caixão practices as much in strategies of plans construction. Those analytical exercises ...

Este estudo tem respaldo teórico-metodológico no campo da Análise do discurso de origem francesa e seus desdobramentos no Brasil, tomando como eixo as noções de memória discursiva, intericonicidade e subjetividade. O corpus base de nossa pesquisa é composto por excertos dos filmes da trilogia de Zé do Caixão, de José Mojica Marins, a saber: À meia-noite levarei sua alma (1964), Esta noite encarnarei no teu cadáver (1967) e Encarnação do demônio (2008), tendo em vista o objetivo de compreender a produção de horror por meio da memória discursiva na materialidade dos filmes que nos propusemos a analisar. As cenas foram selecionadas considerando os elementos clássicos das narrativas de horror, observados tanto na literatura como no cinema, e aqueles que revelam a singularidade artística da obra do diretor brasileiro. Investigamos e discutimos a produção de horror na materialidade discursiva, considerando as noções de memória e intericonicidade. Para alcançar esse objetivo, inicialmente, estudamos a materialidade discursiva da visualidade fílmica, a fim de depreender uma regularidade no funcionamento discursivo das estratégias cinematográficas. Em seguida, refletimos sobre o discurso horrífico como práticas historicamente situadas, avaliando a ordem do discurso na cenografia e na trilha sonora do período da segunda metade do século XX e início do século XXI. Depois, investigamos a produção de sentido de horror na materialidade do cinema, considerando as noções de memória e intericonicidade na visualidade dos filmes. Assim, fomos guiados pelas seguintes questões: a) quais são os deslocamentos teórico-metodológicos necessários para analisar o funcionamento discursivo de estratégias cinematográficas; b) como elas produzem subjetividades no diálogo entre discursos na visualidade fílmica; e c) como a materialidade discursiva do objeto fílmico faz retornar discursos e produz sentidos horríficos ...
Keywords: Cinema brasileiro; Memoria; Subjetividade; Filmes de terror; Análise do discurso; Discourse analysis